A Facile Synthesis of Hematite Nanorods from Rice Starch and Their Application to Pb(II) Ions Removal. Issue 13 (2nd April 2019) - Hoque, Md. Ikram Ul; Yamauchi, Yusuke; Naidu, Ravi; Holze, Rudolf; Saidur, Rahman; Qu, Qunting; Rahman, Mohammad Mahmudur; Torad, Nagy L.; Hossain, Md. Shahriar A.; Kim, Minjun; Kim, Jeonghun; Ahmad, Syed Haseeb Ali; et al.
Abstract: 1D hematite ( α ‐Fe2 O3 ) nanorods were synthesized in the presence of rice starch solution. The size of the nanorods was about 250 nm and 50 nm in length and diameter, respectively. The synthesized nanorods possessed a single α ‐Fe2 O3 phase without any impurities and crystal defects. The obtained hematite nanorods were employed as an adsorbent for lead (II) removal. The isotherms and kinetic studies indicated that our material would be a potential candidate for heavy metal adsorption and removal. Abstract : We report the synthesis of 1D hematite ( α ‐Fe2 O3 ) nanorods in the presence of rice starch solution. The size of the nanorods is about 250 nm and 50 nm in length and diameter, respectively. The obtained hematite nanorods are employed as an adsorbent for lead (II) removal. The isotherms and kinetic studies indicate that our material would be a potential candidate for heavy metal adsorption and removal.